Determination of heavy metals of Sarawak river sediments - Shamira, Shafie (Universiti Malaysia Sarawak, UNIMAS, 2009)
Concentrations of eight heavy metals i.e. Zn, Cu, Ni, Fe, Co, Cd, Mg, and Pb were examined in the river sediments of the Sarawak River, Sarawak using atomic absorption spectroscopy (AAS) in order to evaluate the contamination levels within the sediments. This study also aimed to determine the relationship between the concentration of heavy metals and sediment parameters such as pH and particle size. The mean concentration of heavy metals in the river sediment were found to be in the following order Fe>Mg>Zn>Pb>Ni>Co>Cu.